Pelatihan Desain UI/UX untuk Siswa Kelas XI TKJ SMKN 3 Bangkalan Menggunakan Figma - Vika Dwi Nur Romadhoni; Muhlis Tahir; Dicky Wahyu Pratama; Abdullah Bachtiar Rifai; Febi Feri Andini; Asnanur Rohmah; Aisyah Akmal Hamidillah (Unity Academy, 2024)
This community service aims to improve the UI/UX design skills of 11th grade Computer and Network Engineering (TKJ) students at SMKN 3 Bangkalan, with a focus on training in the use of Figma design applications. The rapid development of digital technology demands design skills that are relevant to industry needs, one of which is in the field of UI/UX, which is key in creating effective and easy-to-use applications and websites. Based on initial observations, SMKN 3 Bangkalan students have a basic understanding of design software, but have not mastered the use of popular industrial design tools such as Figma. The methods applied in this service include preparation, implementation, and evaluation, with materials that include an introduction to UI/UX concepts, the use of Figma, and interface design practices. The workshop was attended by 31 students who showed high enthusiasm, and as a result students were able to create a landing page design that illustrated an understanding of UI/UX principles. In addition to improving technical skills, this activity also opens students' insights regarding career opportunities in the field of digital design. The results of this service are expected to prepare students to face the demands of the world of work and industrial development.